2018
DOI: 10.1007/s10549-018-4776-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding racial/ethnic differences in breast cancer-related physical well-being: the role of patient–provider interactions

Abstract: IPC domains, including those capturing perceived discrimination, respect, and clarity of communication, appeared to partly explain PWB differences for black and Asian women. Results highlight opportunities to improve providers' interactions with minority patients, and communication with minority patients about their supportive care needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…This, in turn, would enable the timely identification of symptoms for which there are evidence‐based interventions. Our findings support attention to patient‐clinician interactions that are patient‐centered and focus on quality of life as well as effective symptom management with particular attention paid to cultural sensitivity 32,41 . Further research is needed to explore approaches to encouraging and enabling patient‐provider communication on symptom severity in ways that are actionable in real‐world clinical practice.…”
Section: Discussionsupporting
confidence: 53%
“…This, in turn, would enable the timely identification of symptoms for which there are evidence‐based interventions. Our findings support attention to patient‐clinician interactions that are patient‐centered and focus on quality of life as well as effective symptom management with particular attention paid to cultural sensitivity 32,41 . Further research is needed to explore approaches to encouraging and enabling patient‐provider communication on symptom severity in ways that are actionable in real‐world clinical practice.…”
Section: Discussionsupporting
confidence: 53%
“…For example, some research has focused support from specific types of people (e.g., family and providers), but not many have not simultaneously assessed support from multiple types of people (see [38,42] as exceptions). While it may be possible to make such comparisons via reviews, studies focusing on support provided by healthcare professionals sometimes use different terminology (e.g., information provision [43]) and/or focus on communication styles [44][45][46] rather than the support provisioned. These differences in focus may make it challenging to compare evidence regarding provider versus nonprovider support.…”
Section: Microsocial Factors Have Been Empirically Well-studied In the Context Of Cancer Survivorship And Survivalmentioning
confidence: 99%
“…As expected, symptom burden was considerably lower than in previous studies in which assessments were taken after chemotherapy started. 16 , 17 , 18 , 23 , 25 We found race-based differences in reported symptoms, with White women reporting more severe distress symptoms and Black women reporting more severe symptoms typically associated with chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 66%
“… 8 , 11 , 12 , 13 , 14 Several studies compared symptoms during or after chemotherapy by race/ethnicity and found mixed results. 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Symptom assessment timing varied in these studies (eg, during treatment vs later in survivorship), which may explain the inconsistent findings. To our knowledge, no studies have compared differences in patient-reported symptoms before starting chemotherapy.…”
Section: Introductionmentioning
confidence: 93%